2022
DOI: 10.1021/acsomega.2c02971
|View full text |Cite
|
Sign up to set email alerts
|

Production of γ-Aminobutyrate (GABA) in Recombinant Corynebacterium glutamicum by Expression of Glutamate Decarboxylase Active at Neutral pH

Abstract: γ-Aminobutyrate (GABA) is an important chemical by itself and can be further used for the production of monomer used for the synthesis of biodegradable polyamides. Until now, GABA production using Corynebacterium glutamicum harboring glutamate decarboxylases (GADs) has been limited due to the discrepancy between optimal pH for GAD activity (pH 4.0) and cell growth (pH 7.0). In this study, we developed recombinant C. glutamicum strains expressing mutated GAD from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
(143 reference statements)
0
8
0
Order By: Relevance
“…γ-Aminobutyric acid (GABA) is a non-protein amino acid commonly distributed in animals, plants, and microorganisms. GABA is an essential inhibitory neurotransmitter in the brain and possesses various physiological functions, such as anti-hypertension, , anti-depression, anti-diabetes, , and immunity improvement . The demand for GABA is increasing because of its accelerated development as a dietary supplement and functional medicine treating certain neurological disorders. , Currently, GABA is mainly produced by chemical synthesis, plant enrichment, and microbial fermentation. The chemical synthesis of GABA has severe health risks, such as using toxic chemical reagents, resulting in a prohibition of its usage as a food additive .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…γ-Aminobutyric acid (GABA) is a non-protein amino acid commonly distributed in animals, plants, and microorganisms. GABA is an essential inhibitory neurotransmitter in the brain and possesses various physiological functions, such as anti-hypertension, , anti-depression, anti-diabetes, , and immunity improvement . The demand for GABA is increasing because of its accelerated development as a dietary supplement and functional medicine treating certain neurological disorders. , Currently, GABA is mainly produced by chemical synthesis, plant enrichment, and microbial fermentation. The chemical synthesis of GABA has severe health risks, such as using toxic chemical reagents, resulting in a prohibition of its usage as a food additive .…”
Section: Introductionmentioning
confidence: 99%
“…γ-Aminobutyric acid (GABA) is a non-protein amino acid commonly distributed in animals, plants, and microorganisms. 1 3 GABA is an essential inhibitory neurotransmitter in the brain and possesses various physiological functions, such as anti-hypertension, 4 , 5 anti-depression, 6 anti-diabetes, 7 , 8 and immunity improvement. 9 The demand for GABA is increasing because of its accelerated development as a dietary supplement and functional medicine treating certain neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Baritugo et al have investigated recombinant C. glutamicum strain (co-expression of the gadB mutant gene and the xylAB gene-encoding xylose isomerase and glucokinase) produced 35.47 g/L of GABA at the medium of glucose and xylose as the substrate. It concluded that two ample fermentative sugars in lignocellulose such as glucose and xylose can be co-utilized by C. glutamicum (Son et al 2022 ).…”
Section: Gaba-producing Strains and Metabolic Pathwaymentioning
confidence: 99%
“…γ-Aminobutyric acid (GABA), a nonproteinogenic amino acid synthesized from l -glutamate by glutamate decarboxylases (GADs), finds application in various areas, such as pharmaceuticals and as a component for biodegradable polymers. , GABA can also be used to synthesize 2-pyrrolidone, a monomer essential for creating nylon-4. , Conventional methods for biosynthetic GABA production have primarily relied on l -glutamate as a substrate for enzymatic or whole-cell reactions using GADs. However, recent research has explored the possibility of producing GABA using relatively cost-effective feedstocks, such as glucose and glycerol, instead of glutamate through direct fermentative production. However, despite several efforts to produce GABA from glycolytic carbon sources, carbon loss resulting from the sequential decarboxylation of isocitrate and glutamate remains a limiting factor for economic production. Given the inevitable carbon loss in the biobased production of GABA, there is a growing interest in harnessing even more economical substrates, such as acetate and C1 gas. Nonetheless, gaseous resources encounter challenges in mass transfer during chemical production processes, which acts as a rate limitation for highly efficient chemical production.…”
Section: Introductionmentioning
confidence: 99%